The Impact of Regulations on Social Protection Integration within the United Arab Emirates Value-Added Tax - Ibrahim Al Shawabkeh; Enas AlQodsi; Mouaid Al Qudah (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2026)
Value-Added Tax (VAT) was introduced in the United Arab Emirates as part of a fiscal reform strategy aimed at diversifying state revenue sources and strengthening the sustainability of the non-oil economy. Although VAT primarily functions as an instrument for generating state revenue, VAT regulations in the UAE also demonstrate the integration of social protection dimensions through the implementation of zero-rated supplies and tax exemptions for strategic sectors. However, there has been limited research examining whether these policies have been effective. Therefore, this study aims, first, to analyze the extent to which UAE legislators have accommodated social protection aspects within VAT regulations; second, to identify the forms and challenges of integrating social protection into VAT implementation; and third, to formulate an ideal regulatory model capable of balancing revenue optimization, fiscal justice, and sustainable economic development. This study employs normative legal research using statutory, comparative, and conceptual approaches. The findings indicate that, first, VAT regulations in the UAE have undergone a functional transformation into an instrument of social protection intended to reduce the regressive impact of consumption taxes and maintain public access to basic necessities. Second, the effectiveness of integrating social protection within the VAT system continues to face several challenges, including administrative complexity, selective and conditional regulations, and limited public tax literacy. Therefore, more adaptive regulatory reforms, simplification of administrative procedures, and policy harmonization among government institutions are required to ensure that the VAT system functions more effectively, equitably, and sustainably.